Framework for the Expansion of the Local Environmental Observer network - Arctic Contaminants Action Program (ACAP) (Arctic Council Secretariat, 2017)
The project steering committee has taken a phased approach to the development of a Circumpolar Local Environmental Observer Network. Phase One activities are on track to be completed and delivered to the Arctic Council Ministers at the May 2017 Ministerial in Fairbanks, Alaska. Community-based monitoring networks in rural communities can help connect those with indigenous, traditional, local and ecological knowledge with scientists, policymakers and technical experts to develop trust, collaborative approaches, and solutions to human health and environmental problems resulting from contaminants and pollution. Strengthening this cooperation and increasing collaboration will bring benefits to commmunities across the Arctic.